Pancreatic adenocarcinoma with histologically proven portal vein infiltration: what is the outcome?. Issue 12 (December 2018) - Martin, David; Petermann, David; Fontanella, Sara; Pu, Yan; Halkic, Nermin; Demartines, Nicolas; Schäfer, Markus
Abstract : Objectives: Technical feasibility and safety of portal vein (PV) and superior mesenteric vein (SMV) resection during pancreaticoduodenectomy (PD) for cancer has been confirmed, but oncological benefits remain unclear. The present study aimed to explore the long-term outcomes of PD with PV/SMV resection and proven histologically invasion. Patients and methods: A total of 95 consecutive PD were performed between January 2008 and August 2013, and 29 patients underwent PV/SMV resection with histologically proven venous tumor infiltration. Patients were matched 1 : 1 to controls who did not undergo venous resection, based on demographic and tumor characteristics. Results: Disease-free survival (DFS) of the PV/SMV invasion group and control group was 9.5 and 7.6 months, respectively ( P =0.51). Median survival and survival at 1, 3, and 5 years were 12.9 months, 59, 17, and 10%, respectively, in case of PV/SMV invasion compared with 20.3 months, 72, 31, and 10%, respectively in control group ( P =0.13). Patients with complete transmural infiltration presented nonsignificantly shorter DFS (9.0 months) compared with those with partial venous wall infiltration (18.4 months, P =0.78). Conclusion: Histologically proven portal venous invasion in patients undergoing PD for adenocarcinoma seemed not to have an effect on both DFS and overall long-term survival.